2019
DOI: 10.1111/ggi.13717
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, arthritis, urinary incontinence, poor self‐rated health, higher body mass index and lower handgrip strength are associated with falls among community‐dwelling middle‐aged and older adults: Pooled analyses from two cross‐sectional Malaysian datasets

Abstract: Aim The identification of risk factors associated with comorbidities and physical fitness might provide pathways for planning therapeutic targets for future falls prevention. Results from large datasets that examined falls risk factors in Asia have been limited. The aim of the present study was to identify the risk factors for falls by pooling data consisting of medical history, physical performance and self‐rated health from two large Malaysian epidemiological studies. Methods Matching variables from the Towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
(41 reference statements)
4
18
0
Order By: Relevance
“…Besides, strengthening of lower limb muscles has been reported to be effective in preventing falls in older adults [35]. Similarly, we have demonstrated that muscle strength was associated with falls among Malaysian community-dwelling older adults in our earlier pooled data ndings [36].…”
Section: Discussionsupporting
confidence: 67%
“…Besides, strengthening of lower limb muscles has been reported to be effective in preventing falls in older adults [35]. Similarly, we have demonstrated that muscle strength was associated with falls among Malaysian community-dwelling older adults in our earlier pooled data ndings [36].…”
Section: Discussionsupporting
confidence: 67%
“…Diabetes mellitus was a prominent risk factor of falls among the population included in the NHMS 2018 confirming the findings of previous local studies. 4,14 A meta-analysis found that older persons with diabetes mellitus had a 64% greater risk of falls with an overall increased risk of 94% and 27% among those who are insulin and non-insulin treated respectively. 25 In a study conducted in Japan among individuals aged ≥60 years, individuals with diabetes hypoglycemia are more likely to experience multiple falls.…”
Section: Discussionmentioning
confidence: 99%
“…1 Risk factors of falls that have been identified include gender, age, education, living situation, history of falling, fear of falling, various health conditions including muscle weakness, joint paints, vertigo, diabetes mellitus, hypertension, cancer, arthritis, osteoporosis, psychiatric disorders, urinary incontinence, poor self-rated health, higher body mass index, lower handgrip strength, visual disorders, gait and balance impairments. [4][5][6][7][8] Difficulties in performing activities of daily living (ADL) and instrumental ADL (IADL) were also identified as possible risk factors for falling accidents among older persons. [6][7][8][9] Medication use is also associated with an increased risk of falls among older persons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations